KINERJA ROOM BOY PADA DEPARTMENT HOUSEKEEPING DI HOTEL GRAND JATRA PEKANBARU - Puty Chairunnisa; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Hotel Grand Jatra Pekanbaru is a five-star hotel located at Jalan Tengku Zainal Abidin No. 1 Pekanbaru Mall Complex, Pekanbaru. The purpose of this study is to determine the performance of the room boy in the housekeeping department at the Grand Jatra Hotel Pekanbaru by using a mixed method with a descriptive approach. Respondents were set at 10 hotel guests. Data collection techniques used are questionnaires, interviews, documentation and observation. With this research, it is shown that the performance criteria factors that affect the performance of rooms at the Grand Jatra Hotel Pekanbaru are the quality of work, quantity of work, supervision, attendance or employee discipline and conservation. Factors Performance appraisal criteria that affect the performance of room boy is supervision with improvement indicators. Keywords: performance, room boy, housekeeping, hotel